Production Cross Sections of Axion in a Static Electromagnetic Field - Soa, Dang Van; Tham, Tran Dinh (Communications in Physics, 2013)
Photon - axion conversions in staticelectromagnetic fields of the size \(a× b × c\) areconsidered in detail by the Feynman diagram methods. Thedifferential cross sections are presented and the numericalevaluations of the total cross section are given. Our result showsthat the conversion cross-sections in the electric field are quitesmall, while in the strong magnetic field, the cross-sections are much enhanced, which can be measurable in current experiments.